Automated Measurement of Blood Vessels in Tissues from Microscopy Images. Issue 1 (10th October 2016) - Kelly, Neil J.; Dandachi, Nadine; Goncharov, Dmitry A.; Pena, Andressa Z.; Radder, Josiah E.; Gregory, Alyssa D.; Lai, Yen‐Chun; Leme, Adriana S.; Gladwin, Mark T.; Goncharova, Elena A.; St. Croix, Claudette M.; Shapiro, Steven D.
Abstract: The quantification of tunica media thickness in histological cross sections is a ubiquitous exercise in cardiopulmonary research, yet the methods for quantifying medial wall thickness have never been rigorously examined with modern image analysis tools. As a result, inaccurate and cumbersome manual measurements of discrete wall regions along the vessel periphery have become common practice for wall thickness quantification. The aim of this study is to introduce, validate, and facilitate the use of an improved method for medial wall thickness quantification. We describe a novel method of wall thickness calculation based on image skeletonization and compare its results to those of common techniques. Using both theoretical and empirical approaches, we demonstrate the accuracy and superiority of the skeleton‐based method for measuring wall thickness while discussing its interpretation and limitations. Finally, we present a new freely available software tool, the VMI Calculator, to facilitate wall thickness measurements using our novel method. © 2016 by John Wiley & Sons, Inc.